PHARMACEUTICAL PRONIOSOMAL DRUG DELIVERY: A COMPLETE REVIEW OF NEW DELIVERY SYSTEM - Maurya, Priyanka; Fatma, Saman; Mishra, Jai Narayan; Kushwaha, Ashutosh (IJRDO-Journal of Applied Science, 2022)
Numerous issues arise in the field of solubility augmentation. Pharmacosomes, a revolutionary method based on lipid medication delivery, have emerged. Pharmacosomes are covalently bound, colloidal, nanometric-size micelles, vesicles, or hexagonal assemblies of colloidal drug dispersions to the phospholipid. Due to their special qualities such tiny size, amphiphilicity, active drug loading, high entrapment efficiency, and stability, they serve as suitable carriers for drug administration fairly accurately. In addition to lowering therapy costs, drug leakage and toxicity, increasing the bioavailability of poorly soluble medications, and having restorative benefits, they aid in the regulated release of pharmaceuticals at the site of action. This medication delivery system's capabilities have expanded to accommodate more medicines.